Model Based Evaluation for the Anaerobic Treatment of Corn Processing Wastewaters - Ersahin, Mustafa Evren; Insel, Guclu; Dereli, Recep Kaan; Ozturk, Izzet; Kinaci, Cumali (Wiley, 2007)
AbstractThe objective of this study was to implement a process model to simulate the dynamic behavior of a full‐scale anaerobic reactor treating corn processing wastewaters under mesophilic conditions. For this purpose, the IWA Anaerobic Digestion Model No.1 (ADM1) was applied to an expanded granular sludge bed reactor of an industrial wastewater treatment plant. The plant has a wastewater treatment capacity of 1594 m3/day. Sensitivity analysis showed that the influent characterization, based on disintegration into carbohydrates, proteins, lipids and inert components, had a large impact on the model outputs. An efficient correlation obtained between the measured and the simulated data, including effluent COD, pH and methane production, highlights good parameter optimization and wastewater characterization. This paper demonstrates a practical example for the application of the ADM1 to an agro‐industrial full‐scale anaerobic reactor.